Techniques and Quality Translation of Interrogative Sentence Dubbing: English-Indonesian and English-Arabic in The Cartoon Movie - Cahyanti, Aisyah Nur; Malik, Abdul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This article aims to describe the types of interrogative sentences in The Spongebob Movie: Sponge on The Run, translation techniques, and the quality of the translation results. The method used is descriptive qualitative. The results of this research are as follows: Based on the translation, interrogative sentences are divided into two types: translations without a shift of 137 data and translations with a shift of 20 data. In this research, it was found that 16 of the 18 translation techniques in the Molina & Albir version were dominated by common equivalent techniques, namely 187 data (41%) in TL 1 and 245 data (46%) in TL 2. Of the 157 data, 113 quality data were found in English-Indonesian dubbing with a score of 2.73 and 115 data in English-Arabic with a score of 2.69. So, the quality results of the dubbing translation of English-Indonesian and English-Arabic question sentences are included in the excellent category. It can be concluded that shifts and translation techniques influence the results of translation quality.